Frequency and prognostic impact of mutations in SRSF2, U2AF1, and ZRSR2 in patients with myelodysplastic syndromes - Thol, Felicitas; Hofmann, Wolf-Karsten (Blood, 2012)
Mutations in genes of the splicing machinery have been described recently in myelodysplastic syndromes (MDS). In the present study, we examined a cohort of 193 MDS patients for mutations in SRSF2, U2AF1 (synonym U2AF35), ZRSR2, and, as described previously, SF3B1, in the context of other molecular markers, including mutations in ASXL1, RUNX1, NRAS, TP53, IDH1, IDH2, NPM1, and DNMT3A. Mutations in SRSF2, U2AF1, ZRSR2, and SF3B1 were found in 24 (12.4%), 14 (7.3%), 6 (3.1%), and 28 (14.5%) patients, respectively, corresponding to a total of 67 of 193 MDS patients (34.7%). SRSF2 mutations were associated with RUNX1 (P < .001) and IDH1 (P = .013) mutations, whereas U2AF1 mutations were associated with ASXL1 (P = .005) and DNMT3A (P = .004) mutations. In univariate analysis, mutated SRSF2 predicted shorter overall survival and more frequent acute myeloid leukemia progression compared with wild-type SRSF2, whereas mutated U2AF1, ZRSR2, and SF3B1 had no impact on patient outcome. In multivariate analysis, SRSF2 remained an independent poor risk marker for overall survival (hazard ratio = 2.3; 95% confidence interval, 1.28-4.13; P = .017) and acute myeloid leukemia progression (hazard ratio = 2.83; 95% confidence interval, 1.31-6.12; P = .008). These results show a negative prognostic impact of SRSF2 mutations in MDS. SRSF2 mutations may become useful for clinical risk stratification and treatment decisions in the future.
First edition: March 2, 2012
Gesehen am 12.10.2018